Moral Chivalry: Gender and Harm Sensitivity Predict Costly Altruism. (August 2016) - FeldmanHall, Oriel; Dalgleish, Tim; Evans, Davy; Navrady, Lauren; Tedeschi, Ellen; Mobbs, Dean
Moral perceptions of harm and fairness are instrumental in guiding how an individual navigates moral challenges. Classic research documents that the gender of a target can affect how people deploy these perceptions of harm and fairness. Across multiple studies, we explore the effect of an individual's moral orientations (their considerations of harm and justice) and a target's gender on altruistic behavior. Results reveal that a target's gender can bias one's readiness to engage in harmful actions and that a decider's considerations of harm—but not fairness concerns—modulate costly altruism. Together, these data illustrate that moral choices are conditional on the social nature of the moral dyad: Even under the same moral constraints, a target's gender and a decider's gender can shift an individual's choice to be more or less altruistic, suggesting that gender bias and harm considerations play a significant role in moral cognition.